Sentidos e efeitos da noção de competência sobre práticas docentes no contexto de cursos superiores de tecnologia - Rosa, Rúbia Simone Valadares (Universidade do Vale do Rio dos Sinos, 2011)
The objective of this study was to investigate and analyze the meanings attributed by professors in Colleges of Technology to the notion of competence, as well as the possible effects of the concept (for those courses taken in the post-professional education reform) on the practices of those professors. The sample involved was compounded by ten professors working in professional education, specifically in Colleges of Technology, from an institution in the System-S-SENACRS Technology College, and throughout their professional careers followed the Reform of Vocational Education. Both the Higher Education Institution, the professors were chosen by certain criteria. The research was based on a qualitative approach and relied on Minayo (2002). The instrument for data collection was a closed survey, organized in two main themes that contained questions on perception of the concept of competence for professors, the implications of the concept of competency in teaching practices of teachers. To that end, we initially performed a literature authors dealing with the conception of competence, their origin, their different modes of interpretation as well as its ownership in several areas, among Kuenzer (2002), Ramos (2002); Deluiz (2001), Zarafian (2003), and the legal documents governing the devices related to vocational education in the LDB 9394/96, as the Federal Decree No. 2.208/97 and Decree No. 5.154/2004. During the review process it was able to identify the axes established in this research that professors perform their teaching practices in education influenced by the notion of responsibility assumed by them and Colleges of Technology. And also it was evidenced that notion of responsibility assumed by these professors is approaching, as Deluiz (2004, 2001a), Ramos (2005, 2004, 2002), with the notion of conceptual competence constructivist viewed that it is similar to the concept discussed the official documents of MEC. This vision includes the skills, while actions and mental operations that articulate knowledge (knowledge, information articulated operatively, skills, or know-how developed cognitively and socio-affective and the values and attitudes (knowledge being, predisposition for decisions and actions built from aesthetic references, political and ethical) which consist of an articulated and mobilized in professional relationships with required quality standards or distinctly normal productions from a professional field. The results indicate the need for exhausting and return the discussions about the notion of competence and the implications that elapse from it in the daily teaching practices.
Keywords: Noção de competência; Educação profissional; Práticas pedagógicas; Notion of competence; Profissional; Education; ACCNPQ::Ciências Humanas::Educação